If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(b + -4) = -2 Reorder the terms: -3(-4 + b) = -2 (-4 * -3 + b * -3) = -2 (12 + -3b) = -2 Solving 12 + -3b = -2 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -3b = -2 + -12 Combine like terms: 12 + -12 = 0 0 + -3b = -2 + -12 -3b = -2 + -12 Combine like terms: -2 + -12 = -14 -3b = -14 Divide each side by '-3'. b = 4.666666667 Simplifying b = 4.666666667
| 6(-6x+8)=-6(9x-5) | | 39x^2-4x-3= | | 5x+3=2(3+x) | | 4/5=6/r-1 | | (3x+5)(5x+8)=0 | | 100x+60x=2000 | | 2.5X+10= | | 2/8=x-3/4 | | .5(4x-6)=-1+3x | | 7/k-5=5/8 | | y+9=6x | | 3x^2-132+12=0 | | x-8/7=7/3 | | (x+4)+(x-3)+x=19 | | b+12.4=19.8 | | 7/a-8=8/2 | | 5x+3(2x-4)=43 | | 3v^2-2v-4=0 | | 2.5y+5= | | 9y-8y+3y= | | 18-(2x+8)=14 | | n-3n=13-4n | | -4y=-4x+10 | | n+5/7=2/3 | | 3x=y+11 | | 3.5+10m=7.98 | | 7r^2+6r+1=0 | | x+7/7=8/4 | | 16-9g=70 | | y=4-38-1.3 | | X+-z=yforz | | 3.5y+8= |